A Single-Nucleotide Polymorphism of αVβ3 Integrin Is Associated with the Andes Virus Infection Susceptibility - Constanza Martínez-Valdebenito; Jenniffer Angulo; Nicole Le Corre; Claudia Marco; VIAL COX, MARIA CECILIA; Juan Miquel; Jaime Cerda; Gregory Mertz; VIAL CLARO, PABLO AGUSTIN; Marcelo Lopez-Lastra; Marcela Ferrés (My University, 2019)
The Andes Orthohantavirus (ANDV), which causes the hantavirus cardiopulmonary syndrome, enters cells via integrins, and a change from leucine to proline at residue 33 in the PSI domain (L33P), impairs ANDV recognition. We assessed the association between this human polymorphism and ANDV infection. We defined susceptible and protective genotypes as “TT” (coding leucine) and “CC” (coding proline), respectively. TT was present at a rate of 89.2% (66/74) among the first cohort of ANDV cases and at 60% (63/105) among exposed close-household contacts, who remained uninfected (p < 0.05). The protective genotype (CC) was absent in all 85 ANDV cases, in both cohorts, and was present at 11.4% of the exposed close-household contacts who remained uninfected. Logistic regression modeling for risk of infection had an OR of 6.2–12.6 (p < 0.05) in the presence of TT and well-known ANDV risk activities. Moreover, an OR of 7.3 was obtained when the TT condition was analyzed for two groups exposed to the same environmental risk. Host genetic background was found to have an important role in ANDV infection susceptibility, in the studied population.
Keywords: andv; snp; psi domain; l33p; rs5918; hantavirus; adult; family characteristics; female; genetic predisposition to disease; genotype; hantavirus; hantavirus infections; humans; integrin alphavbeta3; leucine; male; polymorphism, single nucleotide; proline; prospective studies; risk assessment; risk factors; genomic dna; immunoglobulin m; leucine; proline; vitronectin receptor; leucine; proline; vitronectin receptor; adult; allele; amino acid sequence; andes virus; article; clinical outcome; controlled study; dna extraction; dna polymorphism; gene frequency; genetic association; genotype; human; human cell; infection sensitivity; male; nonhuman; occupation; polymerase chain reaction; prevalence; risk assessment; risk factor; single nucleotide polymorphism; family size; female; genetic predisposition; genetics; hantavirus; hantavirus infection; prospective study